2014
DOI: 10.1111/bpa.12173
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting TP53 Mutations and Immunohistochemistry—A Comparative Study in 157 Diffuse Gliomas

Abstract: The association between p53 immunohistochemistry and TP53 mutation status has been controversial. The present study aims to re-evaluate the efficacy of p53 immunohistochemistry to predict the mutational status of TP53. A total of 157 diffuse gliomas (World Health Organization grades II-IV) were assessed by exon-by-exon DNA sequencing from exon 4 through 10 of TP53 using frozen tissue samples. Immunohistochemistry with a p53 antibody (DO-7) on paired formalin-fixed paraffin-embedded materials was assessed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 29 publications
4
91
2
3
Order By: Relevance
“…PRC2 is susceptible to either gain- or loss-of-function alterations in malignancy [23]. According to the PRC2 structural basis described in Justin et al [27] (the structural basis of the oncogenic H3K27M inhibition of PRC2), the binding of PRC2 and the nucleosome involves multiple interactions of PRC2 components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRC2 is susceptible to either gain- or loss-of-function alterations in malignancy [23]. According to the PRC2 structural basis described in Justin et al [27] (the structural basis of the oncogenic H3K27M inhibition of PRC2), the binding of PRC2 and the nucleosome involves multiple interactions of PRC2 components.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was positive for IDH1R132H with strong cytoplasmic staining [21]. The ATRX and p53 staining positive cut-off value was 10% nuclear staining [22, 23]. Labeling index evaluation for Ki-67 was based on nuclear staining in tumor cells [24].…”
Section: Patient and Methodsmentioning
confidence: 99%
“…Anti-human PTEN (1: 100, Dako) was used as the primary antibody. The antibody for p53 was prepared using anti-human p53 protein (1: 100, Dako) [18] . The antibody against Ki-67/MIB-1 was an anti-human Ki-67 antigen clone MIB-1 (1: 25, Dako).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…BCL2A1 is a potential biomarker that influences preoperative seizure occurrence and postoperative seizure control in patients with low-grade gliomas (You et al, 2013;Li et al, 2014). TP53 is a pivotal gene frequently mutated in diffuse gliomas and particularly in astrocytic tumors (Takami et al, 2014); CCL2 was among the first identified in gliomas, and it is overexpressed in colon carcinomas. Its silencing inhibits colon cancer cell proliferation or increases the sensitivity to apoptotic stimuli of glioma cells, suggesting an oncogenic role (Carrillode Sauvage et al, 2012).…”
Section: Discussionmentioning
confidence: 99%